Ribosomal Protein S1 Specifically Binds to the 5′ Untranslated Region of the Pseudomonas aeruginosa Stationary-Phase Sigma Factor rpoS mRNA in the Logarithmic Phase of Growth - Ševo, Milica (American Society for Microbiology, 2004)
The rpoS gene encodes the stationary-phase sigma factor (RpoS or σ(s)), which was identified in several gram-negative bacteria as a central regulator controlling the expression of genes involved in cell survival in response to cessation of growth (stationary phase) and providing cross-protection against various stresses. In Pseudomonas aeruginosa, the levels of σ(s) increase dramatically at the onset of the stationary phase and are regulated at the transcriptional and posttranscriptional levels. The P. aeruginosa rpoS gene is transcribed as a monocistronic rpoS mRNA transcript comprised of an unusually long 373-bp 5′ untranslated region (5′ UTR). In this study, the 5′ UTR and total protein extracts from P. aeruginosa logarithmic and stationary phases of growth were used in order to investigate the protein-RNA interactions that may modulate the translational process. It was observed that a 69-kDa protein, which corresponded to ribosomal protein S1, preferentially binds the 5′ UTR of the rpoS mRNA in the logarithmic phase and not in the stationary phase. This is the first report of a protein-rpoS mRNA 5′ UTR interaction in P. aeruginosa, and the possible involvement of protein S1 in translation regulation of rpoS is discussed.